BATIK MERANGIN BANGKO JAMBI: STUDI TENTANG BENTUK, FUNGSI, DAN MAKNA MOTIF - CANDRA PRAMANASARI, Drs. Erwin, M.Sn, Dra.Zubaidah, M.Pd (Universitas Negeri Padang, 2015)
This research aims to describe: form 1), function 2), and meaningMerangin batik motifs. This type of research is a qualitativedescriptive. The primary data source that are spoken directly byinformants, source data taken in the form of written notes (image,recording) derived from informants interviewed, documentation andliterature study. Merangin batik motifs deriving from shape of theflora, fauna and geometric, Merangin batik motifs function consistsof physical function, personal, and social, meanings of Meranginbatik motifs generally describes the long history and rich Meranginantiquity.Kata kunci: Motif, Bentuk, Fungsi, Makna